APPLICATION OF THE THEORY OF AN ACTIVE BIPOLAR AND A PASSIVE FOUR-POLE DURING DEVELOPMENT TRANSFORMER REPLACEMENT CIRCUITS - A.S. Bordyug (Измерение, мониторинг, управление, контроль, 2022)
Background. The transformer is a static electromagnetic apparatus designed to convert an alternating current of one voltage into an alternating current of another voltage of the same frequency. The transformer performs AC voltage conversion and/or galvanic isolation in various applications – electric power, electronics and radio engineering. The transformer has at least two windings, which have a common magnetic conductor and which are electrically isolated from each other. Materials and methods. The development of the scheme given in this article is based on the theory of an active bipolar – a part of an electric circuit isolated relative to two terminals containing an energy source (or compensated sources) and a passive four-pole – a part of the circuit that has two pairs of terminals and does not contain energy sources. A transformer can act as a typical active bipolar, as well as a transformer can act as a passive four-pole. Results.The article presents the development of optimization of transformer substitution schemes, which are convenient for theoretical analysis and in calculation practice. If the question arises – why the specified circuits are effective, then the next answer will follow – since they allow you to obtain the desired ratios of the circuits of the primary and secondary windings easier, faster and allow you not to distort such a parameter as accuracy. Conclusions. Moreover, the logical structure of these relations is so expressive in essence, that it is possible to correct known criteria, as well as the wording of new ones. Consequently, the schemes mentioned in this article will be of interest in production and design developments, as well as in the teaching and methodological plan.